A treatment planning comparison of photon stereotactic ablative radiotherapy and proton beam therapy for the re-irradiation of pelvic cancer recurrence. (January 2022) - Chuter, R.; Glassborow, E.; Speight, R.; Clarke, M.; Murray, L.; Radhakrishna, G.; Lavin, V.; Aspin, L.; Aldred, M; Gregory, S; Richardson, J.; Handley, J.
Abstract: Background: Patients who experience a pelvic cancer recurrence in or near a region that received initial radiotherapy, typically have few options for treatment. Organs at risk (OAR) have often reached their dose constraint limits leaving minimal dose remaining for standard re-irradiation (reRT). However, photon based stereotactic ablative radiotherapy (SABR) has been utilised for reRT with promising initial results although meeting OAR constraints can be challenging. Proton beam therapy (PBT) could offer an advantage. Materials and methods: SABR plans used for treatment for ten pelvic reRT patients were dosimetrically compared to PBT plans retrospectively planned using the same CT and contour data. PBT plans were created to match the CTV dose coverage of SABR treatment plans with V100% ≥95%. An 'as low as reasonably achievable' approach was taken to OAR tolerances with consideration of OAR dose from the initial radiation (using equivalent dose in 2 Gy fractions). Results: Dosimetric comparison of relevant OAR statistics showed a decrease in OAR dose using PBT over SABR in all patients, with equivalent target coverage. The largest statistically significant reduction was seen for the colon D0.5 cm 3 with a median reduction from 13.1 Gy to 5.9 Gy. There were statistically significant dose reductions in the median dose to small bowel, sacral plexus and cauda equina. Conclusion: PBT has the potential for significant dose reductions for OARs in the pelvic reRT setting compared to SABR. However, it remains unclear if the magnitude of these OAR dose reductions will translate into clinical benefit.